THE DEFINITION ACCORDING TO THE RESULTS OF THE SEA TRIALS OF THE FATIGUE STRENGTH OF LOAD-BEARING STRUCTURES OF RAILWAY CARS - Blokhin, E. P.; Cherkashyn, Yu. M.; Manashkin, L. O.; Korotenko, M. L.; Myamlin, S. V.; Hranovskyi, R. B.; Horobets, V. L.; Harkavi, M. Ya.; Fedorov, E. F. (Science and Transport Progress, 2005)
The algorithms of treatment of results of working tests of railway carriages with the target of decision of supply of endurance of bearing structural elements are resulted.